2016
DOI: 10.1159/000450679
|View full text |Cite
|
Sign up to set email alerts
|

Use of Direct-Acting Antivirals for the Treatment of Hepatitis C Virus-Associated Oral Lichen Planus: A Case Report

Abstract: Hepatitis C virus (HCV) is frequently associated with various extrahepatic manifestations such as autoimmune features and immune complex deposit diseases. Oral lichen planus (OLP) is one of the representative extrahepatic manifestations of HCV infection. Direct-acting antivirals (DAA) are highly effective and safe for the eradication of HCV. However, there is a lack of information regarding the association between HCV-associated OLP and interferon (IFN)-free DAA therapy. Herein, we present the case of a 60-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
(13 reference statements)
1
18
0
Order By: Relevance
“…From the availability of new direct‐acting anti‐retrovirals (DAAs) for treatment of hepatitis C (Chung et al, ), SVR can reach levels of almost 100% (Liang & Ghany, ), and thus, EHMs can be controlled when the immune tolerance is indirectly restored (Comarmond et al, ). The same has been reported for the treatment of OLP‐HCV, that is, exacerbation of OLP lesions occurs when hepatitis C is treated with interferon and ribavirin (Grossmann, Teixeira, de Aguiar, & do Carmo, ; Nagao, Kawaguchi, Ide, Kumashiro, & Sata, ), and their cure occurs in patients undergoing interferon‐free therapy with DAAs (Misaka, Kishimoto, Kawahigashi, Sata, & Nagao, ; Nagao, Kimura, Kawahigashi, & Sata, ).…”
Section: Discussionsupporting
confidence: 52%
“…From the availability of new direct‐acting anti‐retrovirals (DAAs) for treatment of hepatitis C (Chung et al, ), SVR can reach levels of almost 100% (Liang & Ghany, ), and thus, EHMs can be controlled when the immune tolerance is indirectly restored (Comarmond et al, ). The same has been reported for the treatment of OLP‐HCV, that is, exacerbation of OLP lesions occurs when hepatitis C is treated with interferon and ribavirin (Grossmann, Teixeira, de Aguiar, & do Carmo, ; Nagao, Kawaguchi, Ide, Kumashiro, & Sata, ), and their cure occurs in patients undergoing interferon‐free therapy with DAAs (Misaka, Kishimoto, Kawahigashi, Sata, & Nagao, ; Nagao, Kimura, Kawahigashi, & Sata, ).…”
Section: Discussionsupporting
confidence: 52%
“…We showed that, of patients with OLP, 62% had HCV antibodies and 60% had HCV RNA in their serum [11]. Furthermore, there is evidence that treatment with DAAs improves OLP associated with HCV-related infection [12][13][14][15].…”
Section: Ehime Prefecturementioning
confidence: 78%
“…Local conditions such as poor oral hygiene and smoking may exacerbate the risk of immune stimulation due to increased exposure [31,45]. There are reports about the association of OLP with a number of viral infections such as EBV, VZV, HSV, HPV, CMV, and HIV; the most common evidence of HCV is available [5,31,45,52].…”
Section: Etiologymentioning
confidence: 99%